PENGARUH PERBEDAAN LAMA PERIODE (STARTER - FINISHER) PEMBERIAN PAKAN DAN LEVEL PROTEIN TERHADAP NISBAH DAGING TULANG DAN MASSA PROTEIN DAGING DADA DAN PAHA AYAM PELUNG UMUR 1 MINGGU SAMPAI 11 MINGGU - Samsudin, Muh; Sarengat, Warsono; Nasution, Maulana Hamonangan (Animal Agriculture Journal, 2012)
The study purpose to determine the effect of difference in feeding period (starter – finisher) and protein level meat – bone ratio and protein mass of breast and thigh of pelung chicken from 1 to 11 weeks old of age. The material used was 1 week old chickens pelung with sex between male and female are not distinguishability (mixture) of 96 tail-weight 49.92 +0.35 grams (0.701% CV). Feed used in this study are corn, rice bran, fish meal and broiler concentrate so CP 112. Research using experimental design using Complete Randomized Design (CRD) with 3 treatments ie T1 = treatment by administering Coarse Protein (PK) 18% for 3 weeks and PK 15% for 7 weeks; T2 = treated with PK 18% for 5 weeks and PK 15% for 5 weeks; and T3 = treatment with PK 18% for 7 weeks and then given PK 15% for 3 weeks and each of 8 replicates for each treatment. The parameters observed were feed intake, and feed rate. The results showed that the difference in length of feeding period and protein level no significant effect (P> 0.05) against the ratio of meat and bone mass of the thigh meat protein, while the mass of the protein significantly affect breast meat (P <0.05).Key words: pelung chicken, meat - bone ratio, the mass of the chest and thigh meat protein.